Analysis of Failure Criteria in Laminas Reinforced with Unidirectional Curaua Fiber Fabric - Ferreira,Lucemaide Batista Miranda (2019)
Natural fibers are increasingly used as composite reinforcement in different fields of engineering. Caraua fiber stands out for its good mechanical properties and adherence to resin; however, little is known about its behavior in the manufacture of a composite or whether classic failure theory applies in this case. The present study assesses the mechanical properties of two laminas reinforced with unidirectional curaua fiber containing fiber volume fractions of 30 % and 22 %, and compares the results with the values obtained for four failure criteria, using analysis of variance (ANOVA). To that end, tensile tests were conducted along the fiber direction and at other loading angles, in addition to iosipescu shear tests. The results show that the Hashin criterion was the best and the maximum stress criterion does not represent the failure behavior of these materials.